FFKM sanitary seals enable process plants and manufacturing facilities to operate safely and efficiently. Issue 7 (July 2019) - Atkinson, Simon
Abstract : Dichtomatik Ltd – the authorised UK distributor of the DuPont™ Kalrez® perfluoroelastomer (FFKM) range of materials – is offering new seals that enable process plants and manufacturing facilities to operate safely on a day-to-day basis, whilst improving productivity and process optimisation. This brief focus article highlights the benefits of using these seals which, claims the company, excel in applications involving foodstuffs and pharmaceuticals.